2000
DOI: 10.1074/jbc.m005224200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF) Receptor Superfamily Member TACI Is a High Affinity Receptor for TNF Family Members APRIL and BLyS

Abstract: We also demonstrate that TACI interacts with nanomolar affinity with the BLyS-related tumor necrosis factor homologue APRIL for which no clear in vivo role has been described. BLyS and APRIL are capable of signaling through TACI to mediate NF-B responses in HEK293 cells. We conclude that TACI is a receptor for BLyS and APRIL and discuss the implications for B-cell biology.Members of the tumor necrosis factor superfamily of cytokines play diverse roles in the regulation of cell proliferation, differentiation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
161
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(166 citation statements)
references
References 26 publications
3
161
1
1
Order By: Relevance
“…4 and Tables 1 and 2). WT APRIL bound TACI-and BCMA-Fc, both human and mouse, with affinities comparable with previously published values (Tables 1 and 2) (9,11,12,34). The BCMA-specific mutant R206E bound both human and mouse BCMA with affinities comparable with WT APRIL, whereas its binding to TACI was obviously reduced.…”
Section: Computational Design Of Receptor-selective April Variants-supporting
confidence: 74%
“…4 and Tables 1 and 2). WT APRIL bound TACI-and BCMA-Fc, both human and mouse, with affinities comparable with previously published values (Tables 1 and 2) (9,11,12,34). The BCMA-specific mutant R206E bound both human and mouse BCMA with affinities comparable with WT APRIL, whereas its binding to TACI was obviously reduced.…”
Section: Computational Design Of Receptor-selective April Variants-supporting
confidence: 74%
“…There, XIAP expression was regulated by NF-kB. 31 In that regard, the recent observations 24,25 of enhanced NF-kB activity mediated by APRIL when binding to its receptors TACI or BCMA supports the idea that APRIL-mediated NF-kB activation leads to enhanced levels of XIAP in glioma cells. Of note, protection from death ligand-induced apoptosis in LN-18 glioma cells was insignificant ( Figure 3C), and XIAP expression in LN-18 cells ectopically producing APRIL was not enhanced ( Figure 5B).…”
Section: Discussionmentioning
confidence: 51%
“…24 demonstrated that APRIL binds specifically to TACI and BCMA and thereby activates nuclear factor-kB (NF-kB). Similarly, Wu et al 25 characterized TACI as a receptor for APRIL and reported that TACI mRNA was found predominantly in B cells. In peripheral blood B cells, the interaction of APRIL with its receptors results in enhanced immunglobulin M production.…”
Section: Discussionmentioning
confidence: 99%
“…The recently described TNF-homologue, APRIL (a proliferation-inducing ligand) (Hahne et al, 1998), which is also known as TNF-related death ligand (TRDL1-a) (Kelly et al, 2000) and TNFSF13a, binds B-cell maturation (BCMA) (Laˆabi et al, 1992(Laˆabi et al, , 1994Madry et al, 1998), transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI) (Shu et al, 1999;Gross et al, 2000;Xia et al, 2000) and a hypothetical but as yet uncharacterized third receptor (APRIL-R) (Rennert et al, 2000). B-cell activating factor belonging to the TNF family (BAFF) (Schneider et al, 1999), another TNF-homologue, also binds BCMA , TACI (Marsters et al, 2000;Wu et al, 2000;Yu et al, 2000), in addition to its own specific receptor, BAFF-R (Thompson et al, 2001). APRIL is produced in small amounts in peripheral blood lymphocytes (PBLs) and normal tissue but is produced in much larger quantities in malignant tumours, in which it stimulates the growth of malignant cells (Hahne et al, 1998).…”
Section: Introductionmentioning
confidence: 99%